IMPROVING THE MARKETING PERFORMANCE OF "BOLEN KITA" MSMEs THROUGH DIGITAL MARKETING STRATEGIES - Ismaya, Sakti Brata; Indrajaya, Titus; Purnamasari, Dewi; Mariam, Siti; Rosmiati, Eros (International Journal of Economy, Education and Entrepreneurship (IJE3), 2023)
Abstract The COVID-19 pandemic has provided a significant impetus for Micro, Small and Medium Enterprises (MSMEs) to adopt online business models to survive. Amid these changes, promoting MSMEs through online media, such as Instagram, Facebook, WhatsApp and other social media platforms, has become a common choice. This research focuses on the case of the MSME "Bolen Kita" and aims to investigate the positive impact of digital marketing strategies in improving the marketing performance of these MSMEs. This study uses qualitative and quantitative data analysis techniques to gain insight into how digital marketing strategies have positively impacted the marketing performance of "Bolen Kita" MSMEs throughout the pandemic. The findings of this research will likely provide helpful direction for other MSMEs looking to bolster their presence in today's digital business ecosystem. In the context of the pandemic, digital marketing strategies are an efficient tool for increasing visibility and a critical factor in determining whether micro, small, and medium-sized enterprises (MSMEs) will survive this difficult time.